2018
DOI: 10.1111/cxo.12595
|View full text |Cite
|
Sign up to set email alerts
|

In vivo confocal microscopic investigation of the cornea after autologous implantation of lenticules obtained through small incision lenticule extraction for treatment of hyperopia

Abstract: Purpose: To investigate re-innervation in the implanted lenticule, as well as changes to the cornea, after correcting hyperopia with an autologous implantation of a lenticule obtained through small incision lenticule extraction (SMILE). Methods: This study retrospectively analysed re-innervation in the implanted lenticule, as well as microscopic morphological changes in the corneal architecture of the recipient cornea in five patients (with myopia in one eye and hyperopia in the contralateral eye) who received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Although the femtosecond laser-created photodisruptive process purportedly reduces collateral damage to the corneal stroma, the heat and mechanical effects could create collagen fibrillar derangements at the incisional surface (34). The disturbances presented as increased reflectivity under in vivo confocal microscopy in previous studies and were found to attenuate over time (39,40). The present study is the first to quantify collagen morphology derangement through multiphoton microscopy in the context of examining incisional surfaces created by femtosecond lasers.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Although the femtosecond laser-created photodisruptive process purportedly reduces collateral damage to the corneal stroma, the heat and mechanical effects could create collagen fibrillar derangements at the incisional surface (34). The disturbances presented as increased reflectivity under in vivo confocal microscopy in previous studies and were found to attenuate over time (39,40). The present study is the first to quantify collagen morphology derangement through multiphoton microscopy in the context of examining incisional surfaces created by femtosecond lasers.…”
Section: Discussionmentioning
confidence: 57%
“…10.3389/fmed.2023.1289528 (10,(39)(40)(41). The interface between the lenticule and host stroma may heal and become unnoticeable given sufficient time (14,39,40,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the extensive development of small incision lenticule extraction (SMILE) surgery, the source of SMILE-derived lenticules is abundant and they have become easier to obtain [2][3][4]. A number of studies have preliminarily confirmed the efficacy and safety of SMILE-derived lenticules as a patch graft for the treatment of corneal perforation [5][6][7], hyperopia [8][9][10][11] and keratoconus [12][13][14]. In addition, SMILE-derived lenticules can be used as a good scaffold material to culture corneal cells [15] and construct corneal stroma [16].…”
Section: Introductionmentioning
confidence: 99%
“…At present, freshly obtained corneal stromal lenticules are primarily used in research studies [11,17,18], but investigations have found that immune rejection after keratoplasty is related to the cellular components of corneal allografts [19]. However, the immunogenicity of SMILE-derived lenticules can be reduced by removing some cellular components [20][21][22].Studies have shown that a high concentration of sodium chloride solution combined with nuclease can effectively remove the DNA components of cells in corneal stroma and maintain the structure of the collagen fibers [20].…”
Section: Introductionmentioning
confidence: 99%